The Effect of Combined Problem Based Learning and Scaffolding Models on Students’ Critical Thinking Ability - Widyawati, Dyah; Jamhari, Mohammad; Binti Non Shamdas, Gamar (FKIP Universitas Tadulako, 2023)
This study aims to determine the effect of Combined problem-based learning and scaffolding models on students’ critical thinking ability at SMP Negeri 21 Palu. This type of research is a quasi experiment. The research was conducted in two class groups: class VII and class VIII B as the experimental class. The data collection technique uses purposive sampling. The main instrument used was the 7th-grade of critical thinking essay test which consisted of 8 questions. Data were analyzed by a non-parametric test. It is the Wilcoxon test signed ranks test. Obtained the results that Asymp.Sig (2-tailed) is 0,000 on the critical thinking ability test, H1 is accepted, this means that there is a significant effect of the combined problem-based learning and scaffolding models on the critical thinking ability of students at SMP Negeri 21 Palu in the 2019 / 2020 school year.